Results from a multicentre international registry of familial Mediterranean fever: impact of environment on the expression of a monogenic disease in children. Issue 4 (5th March 2013) - Ozen, Seza; Demirkaya, Erkan; Amaryan, Gayane; Koné-Paut, Isabelle; Polat, Adem; Woo, Pat; Uziel, Yosef; Modesto, Consuelo; Finetti, Martina; Quartier, Pierre; Papadopoulou-Alataki, Efimia; Al-Mayouf, Sulaiman M; et al.
Abstract : Background and aim: Familial Mediterranean fever (FMF) is an autoinflammatory disease caused by mutations of the MEFV gene. We analyse the impact of ethnic, environmental and genetic factors on the severity of disease presentation in a large international registry. Methods: Demographic, genetic and clinical data from validated paediatric FMF patients enrolled in the Eurofever registry were analysed. Three subgroups were considered: (i) patients living in the eastern Mediterranean countries; (ii) patients with an eastern Mediterranean ancestry living in western Europe; (iii) Caucasian patients living in western European countries. A score for disease severity at presentation was elaborated. Results: Since November 2009, 346 FMF paediatric patients were enrolled in the Eurofever registry. The genetic and demographic features (ethnicity, age of onset, age at diagnosis) were similar among eastern Mediterranean patients whether they lived in their countries or western European countries. European patients had a lower frequency of the high penetrance M694V mutation and a significant delay of diagnosis (p<0.002). Patients living in eastern Mediterranean countries had a higher frequency of fever episodes/year and more frequent arthritis, pericarditis, chest pain, abdominal pain and vomiting compared to the other two groups. Multivariate analysis showed that the variables independently associated with severity of disease presentation were country of residence, presence of M694V mutation and positive family history. Conclusions: Eastern Mediterranean FMF patients have a milder disease phenotype once they migrate to Europe, reflecting the effect of environment on the expression of a monogenic disease.